Estilo parental y habilidades sociales en adolescentes de bachillerato de la Unidad Educativa ‘‘Pedro Carbo’’. Bolívar, 2020 - Katherin Estefanía, Sinchipa Tixe (2020)
Parental styles is the way in which parents educate their children by being in charge of imparting values. Nowadays, families has undergone changes in their roles, modifying parenting styles and communication between parents and children, creating inappropriate behaviors of adolescents within their family environment and with their peers, generating conflicts in the progress of their social skills. This research aims to: analyze the parenting style and social skills in adolescents from the “Pedro Carbo” Educational Unit of the Bolívar province. The instruments that were applied to 100 students by the psychologist of the Student Counseling Department are: Baumrind’s Parenting Styles Questionnaire (1994) and Goldstein’s Social Skills Scale (1980), where it could be identified that 52% belong to authoritarian parents, 32% correspond to authoritative mothers. Regarding social skills, it was found that most of the adolescents with 60% belong to a low level of social skills, 25% at a medium level and 15% at a high level, it is necessary to point out that a strict parental style directly affects adolescents, since it prevents their personal and social development. With these results, a therapeutic plan with a cognitive-behavioral approach was carried out with several techniques to improve: relationships between parents and children, academic performance, development of social skills and lifestyle of each adolescent.